ENDF/B-VIII.0-based fast neutron removal cross sections database in Z = 1 to 92 generated via multi-layered spherical geometry. (May 2023) - Hila, Frederick C.; Jecong, Julius Federico M.; Dingle, Cheri Anne M.; Asuncion-Astronomo, Alvie J.; Balderas, Charlotte V.; Sagum, Jennifer A.; Guillermo, Neil Raymund D.
Abstract: A fast neutron mass removal cross sections ( Σ R / ρ ) database covering the elemental range of Z = 1 to 92 is generated for source neutron energy distributions based on 241 Am–Be, 252 Cf, and 235 U. Monte Carlo simulations using ENDF/B-VIII.0 nuclear data were performed with the fast neutron removal theory's ideal spherical representation. The ENDF/B-VIII.0-based Σ R / ρ ′s derived were compared with values from the Oak Ridge National Laboratory's Lid Tank Shielding Facility (LTSF) experiments, values from software Phy-X/PSD and MRCsC, values obtained by an empirical model in Zoller, and values derived using the older ENDF/B-VII.0 nuclear data library. Subsequently, the generated Σ R / ρ ′s were evaluated for convergence under varying moderator thickness. Results indicate that the Σ R / ρ quantity for fission and (alpha, n) spectra is universal, with slight deviations for low Z elements. The Σ R / ρ values generated from ENDF/B-VIII.0 agreed with LTSF experiments with an average relative deviation of 8.58%. Moreover, using ENDF/B-VIII.0-based Σ R / ρ ′s, the derived fast neutron effective removal cross sections ( Σ R 's) for several light compounds and dry concrete have better agreement on average with LTSF experiments compared with values derived from the available Σ R / ρ ′s in the literature. Significant differences were found for Σ R / ρ ′s that were generated with ENDF/B-VIII.0 as compared with the superseded ENDF/B-VII.0. Furthermore, ENDF/B-generated Σ R / ρ ′s through spherical model showed the expected convergence towards singular values at moderator thicknesses practical for fast neutron removal theory applications. Owing to the relatively high unavoidable uncertainties of the LTSF experimental Σ R / ρ ′s, the ENDF/B-VIII.0-based Σ R / ρ ′s present a new and potentially favorable database in Σ R general calculations for homogeneous multi-element materials for point-kernel shielding applications. Highlights: A Σ R / ρ database was produced using the latest ENDF/B via multi-layer sphere model. Produced Σ R / ρ ′s led to calculated Σ R values close to LTSF experimental measurement. All Σ R / ρ ′s for fission and (α, n) neutron source energy spectra were similar. Differences were found in Σ R / ρ ′s produced using 7th and 8th versions of ENDF/B. Convergence of Σ R / ρ ′s at increasing moderator thickness was demonstrated.